Polystemma canisferum (Apocynaceae, Asclepiadoideae): a distinctive new gonoloboid milkweed vine from Sonora, Mexico - Mcdonnell, Angela; Fishbein, Mark (Phytotaxa, 2016)
A new species from Sonora, Polystemma canisferum (Apocynaceae, Asclepiadoideae, Gonolobinae), is described. Polystemma is a segregate of Matelea consisting of species that possess hairs that are filled with a crystalline substance at maturity, filiform or fleshy corona appendages, and fusiform fruits. The new species shares these characters but is distinguished by its unique, narrowly tubular-campanulate green corolla. Images and a distribution map are included.